Producers' valuation of animal welfare practices: Does herd size matter? - Michael Danne; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
It is alleged that larger farms are less willing to adopt animal welfare-friendly production systems, though empirically-based knowledge on this issue is still lacking. Therefore, the aim of this study is to analyze pig and sow producer preferences for the adoption of animal welfare standards (AWS), with primary interest in herd size effects on producers' adoption behavior. A survey was carried out with pig (n = 103) and sow (n = 63) producers in Germany. A discrete choice experiment (DCE) was conducted to analyze herd size effects on producer adoption of AWS. Producers' attitudes about the economic feasibility of animal welfare are affected by the herd sizes. The results of the DCE indicate that larger herd sizes in pig production are correlated with lower adoption of outdoor yards and bedding material, while adoption of the remaining AWS is unaffected by herd size. Sow producers show no herd size-related differences in acceptance of the analyzed AWS. The standard criticism regarding the lack of animal welfare adoption on large farms was not supported by this study. Identifying herd-size effects on the producers' adoption behavior for AWS may be an important step in clarifying the discussion about animal welfare in intensive production systems. Furthermore, the identified heterogeneity in the producers' preferences underlines the need for identification of the most effective animal welfare strategies for farms of various structures without endangering profitability. In this regard, policy is suggested to support strategies that directly improve animal welfare on farms of all sizes instead of targeting a decrease in farm size. The study is the first to demonstrate empirically based knowledge about herd size effects on the farmers' adoption of AWS.
Keywords: 330; animal welfare; herd size; pig production; discrete choice experiment